Implementasi Program Permukiman Transmigrasi Pola Restorasi di Desa Kahingai Kawasan Transmigrasi Belantikan Raya, Kabupaten Lamandau - Suwandi Suwandi; Tresia Kristiana; Faizal Madya (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
The implementation of the pugar pattern transmigration housing development program is expected to provide a sense of justice for local residents because of the equal treatment between TPA and TPS. The purpose of this study is to describe and analyze the implementation program, describe and analyze the roles of government officials in implementing the implementation program, and describe and analyze the factors that influence the implementation program. This study uses a qualitative method with a descriptive approach. The results of the study describe (1) the process of building transmigration residential housing in the village of Kahingai starting from the planning stage, proposing programs, development based on transmigration and placement of transmigrants (2) The role of government officials in the construction of transmigration housing, namely facilitating residents of Kahingai village to obtain the transmigration program pugar, helping to reconcile and find a middle way to problems that arise in the development process and build understanding between stakeholders (3) Factors that influence the Implementation of the Pugar Kahinga Transmigration Settlement Development Program in the Belantikan Raya Area, Lamandau Regency (1) Land Consolidation regulations and SOPs Transmigration for the Development of Transmigration Settlements Pattern of Land Claim Pugar and (3) RTJK that are not inhabited by their owners.